The murderer's ape - Wegelius, Jakob 1966- (Delacorte Press, 2017)
When her best friend, the sailor Henry Koskela, is falsely accused of murder, a gorilla named Sally Jones visits the run-down docks of Lisbon, embarks on a dizzying journey across the seven seas, and calls on the Maharaja of Bhapur's magnificent court...all in an attempt to clear Henry's name
Map on lining pages
Keywords: Mystery and detective stories; Adventure and adventurers; Friendship; Gorilla; Human-animal relationships; Kinderbuch; Jugendbuch